Paradigm of Recodification of Corruption in Criminal Code Against its Designation as Extraordinary Crime - Bahar, Muhamad Ghifari Fardhana; Firdaus, Sendy Pratama; Fairuza, Hanny Hilmia (Universitas Brawijaya, 2024)
In December 2022, the Government and DPR passed Law Number 1 of 2023 concerning the Criminal Code, setting out provisions on corruption previously regulated by special laws. The inclusion of corruption raises the question of whether including articles on corruption in the New Criminal Code will eliminate the title of extraordinary crime and its specificities. This research analyses the effect of the recodification of corruption articles in the New Criminal Code on the specificity of corruption and its designation as an extraordinary crime. This research uses normative research methods by examining the theory of various formal laws and regulations to answer legal issues. The results of his research are as follows: first, the recodification of corruption articles into the New Criminal Code is viewed from the perspective of Lawrence M Friedmann’s Legal System Theory. From the standpoint of legal substance, corruption does not terminate its designation as an extraordinary crime. From the legal structure perspective, corruption may terminate the title of extraordinary crime because there are restrictions on the KPK’s authority to calculate state financial losses. From the standpoint of legal culture, corruption remains an extraordinary crime. Second, the existence of the New Criminal Code affects the concept of punishment regulated in the Anti-Corruption Law, namely, the imposition of the death penalty regarding the death penalty regulated in the Anti-Corruption Law and changing the special minimum threat of Article 2 of the Anti-Corruption Law, which is lower from four to three years.